2019
DOI: 10.5888/pcd16.180681
|View full text |Cite
|
Sign up to set email alerts
|

Age Disparities Among Patients With Type 2 Diabetes and Associated Rates of Hospital Use and Diabetic Complications

Abstract: Introduction Although screening for diabetes is recommended at age 45, some populations may be at greater risk at earlier ages. Our objective was to quantify age disparities among patients with type 2 diabetes in New York City. Methods Using all-payer hospital claims data for New York City, we performed a cross-sectional analysis of patients with type 2 diabetes identified from emergency department visits during the 5-year period 2011–2015. We estimated type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Findings from this study showed that more than three-fourths of patients hospitalized due to type 2 diabetes were more than 60 years of age. This finding aligns with data on diabetes-related hospital admission in other countries [ 6 , 37 , 38 ]. Between 2009 and 2019, the prevalence of comorbidities among patients with type 2 diabetes increased from 75.2% to 78.9% [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Findings from this study showed that more than three-fourths of patients hospitalized due to type 2 diabetes were more than 60 years of age. This finding aligns with data on diabetes-related hospital admission in other countries [ 6 , 37 , 38 ]. Between 2009 and 2019, the prevalence of comorbidities among patients with type 2 diabetes increased from 75.2% to 78.9% [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…While elevated prevalence of comorbidities such as diabetes and hypertension increased the underlying infection fatality rate in in Black and Hispanic/Latino populations, the enormous difference in CFR in younger age groups in Mar-Jun 2020 is unlikely to be explained by comorbidities alone. For example, if diabetes prevalence at age 45 were around 5% in non-Hispanic Whites and 11% in non-Hispanic Blacks (20), and diabetes increased the risk of severe outcomes by around 60% (21), the disparity in diabetes prevalence would increase the CFR in the Black population ages 41-50 by approximately 10%. Yet in this age group, the relative risk of death given a case was almost 300% higher in the Black population compared to White in Mar-Apr 2020 [2.94 (95% CI: 1.72-5.03)].…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the prevalence of T2DM in 11 Asian cohorts found that the highest prevalence of T2DM was observed in the oldest age group (>70 years) in China, and among the age group 60-69 years in Singapore and India (22). Besides, the highest proportion of non-Hispanic blacks with T2DM was in their 50s, more than a decade earlier than non-Hispanic whites (23). It is worth noting that our results suggested that there was no significant statistical difference in the prevalence of T2DM between males and females, and the heredity of T2DM may not be related to sex.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the prevalence of T2DM in 11 Asian cohorts found that the highest prevalence of T2DM was observed in the oldest age group (>70 years) in China, and among the age group 60–69 years in Singapore and India ( 22 ). Besides, the highest proportion of non-Hispanic blacks with T2DM was in their 50s, more than a decade earlier than non-Hispanic whites ( 23 ).…”
Section: Discussionmentioning
confidence: 99%